Raman spectroscopy provides insight into carbonate rock fabric based on calcite and dolomite crystal orientation. (17th March 2021) - Murphy, Ashley E.; Jakubek, Ryan S.; Steele, Andrew; Fries, Marc D.; Glamoclija, Mihaela
Abstract: Carbonate rocks record the oldest forms of life on Earth, and their geologic reconstruction requires multiple methods to determine physical and chemical processes before conclusions of ancient biosignatures are made. Since crystal orientation within rock fabric may be used to infer geologic settings, we present here a complementary Raman method to study the orientation of calcite (CaCO3 ) and dolomite [CaMg (CO3 )2 ] minerals. The relative peak intensity ratio of the carbonate lattice Eg modes T and L reveals the crystallographic orientation of calcite and dolomite with respect to the incident light polarization. Our results for calcite show that when the incident laser light propagates down the crystallographic a / b axis: (1) the L mode is always greater in intensity than the T mode ( I T < I L ), and (2) the spectra are most intense at 45° and least intense at 90° polarization angles measured from around the c axis. Our results for dolomite show that (1) I T > I L when the incident light propagation is down the crystallographic c axis and (2) I T < I L when the incident light propagation is down the crystallographic a / b axis. This study reveals mineral orientation variation related to deposition and paragenesis within limestone and dolostone samples. The method presented yields information related to growth and deformation during diagenetic and metamorphic alteration and may be used in research seeking to identify the fabric parameters of any calcite or dolomite containing rock. The compositional and structural data obtained from Raman mapping is useful in structural geology, materials science, and biosignature research. Abstract : This study introduces a method to qualitatively examine the relative crystallographic orientations of calcite and dolomite solely from their Raman spectral relative intensities. The data can be displayed as an image of relative Raman intensity of the L/v1 and T/L modes across a sample surface. This method enables examination of preferred mineral orientation within rocks, which may yield information related to growth and deformation during diagenetic and metamorphic alteration of any calcite or dolomite containing rocks.